Formulation of medicinal toothpaste from jatropha carcus latex - Ummi Hajira, Khairuddin (2010)
Since many centuries,latex of Jatropha carcus Linn as a plant that cure many illness such as toothache bleeding gum due to antimicrobial activity. The objective of this research are to formulate the medicinal toothpaste using latex of Jatropha Carcus, to test antibacterial activity of this medicinal toothpaste and to determine the stability studies of toothpaste formulation. The genus name jatropha derives from the Greek word jatro’s(doctor) and trophe’(food),which implies medicinal Formulation of medicinal toothpaste from jatropha is the research for improvement dental health products . This toothpaste is invented to defuse which illness due to toothache. Eventhough the latex has been used traditionally as a plant medicament, scientific investigation including toxicological studies was very limited Typical toothpaste formulation contain several components such as abrasive, humectant,surfactant, binder, sweetener, preservatives, water and active ingredients For method analysis, In vitro method is a suitable method toobserve the antimicrobial activities before and after stability test. Evaluation of antimicrobial activity and the stability study of the formulation toothpaste can certainly have promising result. Various weight of active ingredients are been tested which is used five increasing amount of J.curcas Latex ( 312 μg, 625 μg, 1250 μg, 2500 μg, 5000 μg). Zone of inhibition of antimicrobial test is increasing when the amount of active ingredient (J.carcus latex) is increasing. Its shown that latex of jatropha has potential in antimicrobial activity.This formulation is expected to be commercially more viable and effective alternative without significant compromise on the teeth cleaning effect. Therefore the result of this study would be possible reference of toothpaste formulation in Malaysia open markets to reduce oral bacteria toothpaste.